Evaluating the mucolytic effectiveness of Ambroxol and N-Acetylcysteine in patients with Acute exacerbation of chronic obstructive pulmonary disease - Aswin A. Anil; Devendu Rajesh; Aishwarya Laxmi Krishnan; Ciciliya Arun; Rosemary Thomas; Prashant Chandra; Nithya Haridas (Elsevier, 2024)
Introduction: Chronic obstructive pulmonary disease (COPD) is the third most fatal disease globally. Acute deterioration of the patient's respiratory symptoms is known as an acute exacerbation of COPD (AECOPD), that goes beyond usual variations and result in change in medications. Ambroxol (ABX) and N-acetylcysteine (NAC), are mainly used as mucolytics in the treatment of AECOPD. Methodology: This prospective observational study examines effectiveness of ABX and NAC in COPD patients by assessing the quality of cough relief, peak expiratory flow rate (PEFR), length of hospital stay, quality of life (QOL) and reduction in symptoms of COPD. Leicester Cough Questionnaire (LCQ); Breathlessness, Cough and Sputum scale (BCSS)and St. George Respiratory Questionnaire (SGRQ) scales are used to evaluate patient condition before and after the treatment. Results: The mean duration of hospital stay for NAC and ABX were found to be 8 ± 3.6 and 9.9 ± 3.9 days, respectively. Lung function in both groups improved with a change in percentage mean score of PEFR. Reduction in symptoms of COPD was evident in both groups by decrease in mean BCSS score from admission to discharge. Our study also demonstrated better QOL in both groups using SGRQ. LCQ showed a mean increase in all domains: physical, psychological and social. Conclusion: It was concluded that both ABX and NAC leads to betterment in lung function, cough relief and control AECOPD. Hence, this study gives a signal to clinicians about these treatment options along with standard therapy of COPD for a better therapeutic outcome.